Cross linking of collagen is increased in colonic diverticulosis. Issue 1 (July 1995) - Wess, L; Eastwood, M A; Wess, T J; Busuttil, A; Miller, A
Abstract : Development of colonic diverticulosis is a function of age and declining colonic wall mechanical strength. The latter is partly a consequence of changes in the collagen structure. Collagen from unaffected human colons (n = 20, age range 20-80 years) and those with colonic diverticulosis (n = 5, age range 67-80 years) were obtained at necropsy. The total collagen content was measured as the hydroxyproline content and cross linkage by collagen solubility in weak acid was studied. The colonic total collagen content was constant with age (mean (SD) 15.8 (0.3) mg/100 mg wet weight of tissue). The acid solubility of the collagen, however, increased after the age of 40 years: at over 60 years, colonic diverticulosis was associated with an increased acid solubility ratio compared with values in unaffected colons (15.3 (0.2); compared with 9.2 (0.2), p < 0.001). The cross linking of colonic collagen increases with age. These changes seem to be a factor in the aetiology of colonic diverticulosis.